التحري عن جين mecA للمكورات العنقودية الذهبية Staphylococcus aureusالمسببة لالتهاب الثدي - كاظم حميدسميرة; باسم رسول الدباغميادة (University of Thi-Qar Journal of Science, 2019)
128 of pus samples were collected from women’s infected with Mastitis. The identification of the Staphylococcus aureus isolates depended on colonial morphology, microscopic examination and biochemical tests as a primary identification, and detection of found mec A gene using the polymerase chain reaction. The researches to the following results: The results showed that 22 isolates did not appear any growth and percentage (17.19)% whereas 106 (82.81%) isolates belongs to Staphylococcus and 34 from this isolates belongs to Staphylococcus aureus and percentage (32.07)% the research has detected the presence of genetic factor mec A belongs to Staphylococcus aureus (34) where the number of the samples carrying the gene 14 (41.1%).The results also includes a high association between this genetic factor and Methicillin Resistant Staphylococcus aureus (MRSA). Besides, there is also a correlation between MRSA and Mastitis diseases. This study draws attention to the current increase in MRSA in Najaf city which increases the importance of working to develop means of infection control to prevent further spread in the community. جمعت 128 عينة القيح من النساء المصابات بالتهاب الثدي ، شخصت المكورات العنقودية الذهبية بالاعتماد على الصفات المظهرية للمستعمرات والفحص المجهري والفحوصات البايوكيميائية ، والكشف عن وجود الجين mecA في هذه العزلات باستخدام تقنية تفاعل انزيم البلمرة المتسلسل ، حيث توصل هذا البحث الى النتائج التالية :- أظهرت النتائج بأن (22) عزلة لم يظهر فيها نمو وبنسبة(%17.19) و 106 ((82.81%عزلة كانت تابعة للمكورات العنقودية ، و 34 من هذه العزلات كانت تابعة للمكورات العنقودية الذهبية وبنسبة (32.07)% وعند الكشف عن وجود العامل الوراثي mecA للعزلات التابعة للمكورات العنقودية الذهبية (34) كانت عدد العزلات الحاملة للجين14 وبنسبة (41.1) %، ومن نتائج هذه الدراسة يمكن الاستنتاج انه يوجد اقتران شديد بين هذا العامل الوراثي والمكورات العنقودية الذهبية المقاومة للمثيسيلين ، كما يوجد ارتباط بين هذا العامل الوراثي وامراض التهاب الثدي ، كما ان هذه الدراسة تلفت الانتباه الى الزيادة الحالية في حالات الاصابة بالمكورات العنقودية الذهبية المقاومة للمثيسيلين في محافظة النجف الاشرف مما يزيد من اهمية العمل على تحقيق وسائل مكافحة العدوى لمنع المزيد من انتشارها في المجتمع .